Struktur Penceritaan dalam Novel Mualaf Karya John Michaelson: Tinjauan Naratologi Gerard Genette - Fristi Setiawati Oki; Herman Didipu; Jafar Lantowa (Jurnal Sinestesia, 2023)
This study raises the problem of how the story structure in John Michaelson's novel Mualaf is viewed from narrative order, duration, frequency, mode, and narrative sound. The purpose of this research is to describe the story structure in John Michaelson's Novel Mualaf in terms of narrative order, duration, frequency, mode, and narrative voice. This study uses a qualitative descriptive research method. Based on the results of the study, it was found that there were five categories of Gerard Genette'snarratology theory, the first was narrative order, the level of narrative sequence contained in the novel, namely analepsis, the second was found in narrative duration, found the duration of narrative scenes and summaries, the third, in narrative frequency, there was repetition frequency in storytelling. novel, the fourth in the narrative mode of the novel uses internal focalization and in narrative voice seen from the time of telling this novel uses the time of telling of the past, on the person aspect there is a homodiegetic narrator type and on the narrative level of the novel there is an extradiegetic-homodiegetic paradigm.